Shear deformation behavior and failure mechanisms of graphene reinforced Sn-based solder joints bonded by transient current - Li, Yuan; Xu, Lianyong; Zhao, Lei; Hao, Kangda; Han, Yongdian (Materials & design, 2022)
[Display omitted] •Crystal orientation spread and the cracks propagation during shear were observed in situ.•The roles of grain boundary types on the deformation of solder joints were confirmed based on molecular dynamics.•The strengthening mechanisms of graphene on composite solder was firstly quantitatively confirmed. Graphene as a reinforcement is expected to improve the shear strength of solder joint. However, little is known about the deformation behavior and mechanisms of composite solder joints. In this study, sandwich joints are prepared using graphene nanosheets-reinforced Sn-Ag-Cu composite solder (GNSs/SAC) by transient current bonding technology in order to obtain dispersed graphene. Interrupted shear tests combined with orientation image microscopy are conducted at different strain to observe the morphology and crystal orientation evolution of solder joints in situ. Some twins rotate, and the orientation begins to spread during shear, while the orientation of large Sn grain shows a minimal change. Cracks tend to initiate and propagate along the boundary. The failure mechanisms of the solder joint is determined. Molecular dynamics results show that the strain concentration at the boundary. Continuous shear tests show that the shear strength was improved by approximately 50.7% with the addition of 0.1 wt% graphene. Based on microstructure analysis and calculation, load transfer is identified as the dominant strengthening mechanism for GNSs/SAC alloys, followed by Orowan system. Graphene does not refine the grain size of solder joints, and dislocation multiplication from thermal mismatch does not strengthen them.